2017
DOI: 10.1111/jocs.13114
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative intra-aortic balloon pump use in high-risk patients prior to coronary artery bypass graft surgery decreases the risk for morbidity and mortality-A meta-analysis of 9,212 patients

Abstract: Current evidence from RCT and OT suggests beneficial effects for the IABP in high-risk patients before CABG surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 54 publications
4
46
1
4
Order By: Relevance
“…The results regarding the preoperative use of IABP from previous studies have been controversial. For example, a reduced mortality risk, postoperative AMI, and renal failure had been previously described in small-sized RCTs and a meta-analysis [1][2][3][4][5]11]. However, other RCTs have shown no difference in 30-day mortality or morbidity associated with the perioperative use of IABP, whereas more recent studies have argued that the hemodynamic effects of the IABP are modest and do not result in a significant increase in cardiac output, left ventricular stroke work index, or systemic vascular resistance [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results regarding the preoperative use of IABP from previous studies have been controversial. For example, a reduced mortality risk, postoperative AMI, and renal failure had been previously described in small-sized RCTs and a meta-analysis [1][2][3][4][5]11]. However, other RCTs have shown no difference in 30-day mortality or morbidity associated with the perioperative use of IABP, whereas more recent studies have argued that the hemodynamic effects of the IABP are modest and do not result in a significant increase in cardiac output, left ventricular stroke work index, or systemic vascular resistance [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The intra-aortic balloon pump (IABP) is widely used to improve coronary perfusion and prevent complications [5][6][7]. Some recent randomized controlled trials (RCTs) have suggested that IABP insertion does not improve the ventricular function and does not reduce complications in patients with cardiogenic shock after acute myocardial infarction (AMI) [8]; preoperative IABP use may prevent complications in high-risk patients undergoing CABG [9][10][11][12]. A recent meta-analysis suggested that preoperative IABP use is associated with mortality reduction [11], but these findings were mainly derived from small RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Its wide use, however, has been harshly questioned over the last few years, especially by the Shock II trial (Thiele et al., ). This has resulted in much debate regarding the use of this assist device that has been recently refreshed by new literature in favour of the use of IABP in certain pathological conditions (Deppe et al., ; Gelsomino, Johnson, & Lorusso, ; Iqbal et al., ; Ouweneel et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis, for example, included 9212 patients and investigated the utility of the IABP when implanted preoperatively in patients undergoing coronary bypass graft surgery [6]. The results of this analysis strongly indicate that there is benefit in using the IABP under these conditions, with the relative risk reduction of mortality being more than 4%.…”
mentioning
confidence: 99%
“…The results of this analysis strongly indicate that there is benefit in using the IABP under these conditions, with the relative risk reduction of mortality being more than 4%. Furthermore, the risk of MI and renal failure were reduced when IABP treatment was instigated and both intensive care and total hospital stays were reduced, also indicating a possible economic benefit, as well as health benefit, of using the IABP [6]. …”
mentioning
confidence: 99%